Perceived benefits of a multiple family group for children with behavior problems and their families. Issue 3 (3rd July 2019) - Acri, Mary C.; Hamovitch, Emily K.; Lambert, Kate; Galler, Madeline; Parchment, Tyrone M.; Bornheimer, Lindsay A.
ABSTRACT: Multiple family groups (MFG) have shown to have promising results for children with behavioral difficulties. The 4Rs and 2Ss is a curriculum-based multiple family group model for families of children with disruptive behavior disorders, who live in poverty-impacted communities. This study aimed to explore group processes and caregiver perceptions of the benefits of participating in the 4Rs and 2Ss MFG. Caregivers participating in the MFG were asked to complete a 29- item questionnaire which collected information about the perceived benefits of the MFG upon Yalom's therapeutic factors, including group cohesion, universality, interpersonal learning, guidance, catharsis- and self-understanding. Data were analyzed using SPSS 25, and descriptive statistics were performed for each sub-scale. Responses of open-ended questions were reviewed and coded by two of the authors. Thirty-two caregivers completed the survey. Results indicated that the MFG offered multiple benefits that align with Yalom's therapeutic factors, such as creating a sense of universality, catharsis, group cohesion, and interpersonal learning. Future research is needed to determine whether such therapeutic factors are associated with changes in child outcomes and family functioning.